Laser surface hardening effect of ductile iron mold and determination method of hardened layer depth
By analyzing the phase composition of the surface of the ductile iron mold, combining the proportion of martensite and austenite to judge the hardening effect, and analyzing the phase composition along the depth direction to calculate the depth of the hardening layer, the accuracy of determining the depth of the hardening layer and the hardening effect in the prior art is solved, and a simpler and more accurate judgment process is achieved.
Patent Information
- Application Number
- CN202410321682.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-03-20
AI Technical Summary
The existing hardness method and metallographic method have limitations in determining the depth and hardening effect of the laser hardening layer of ductile iron molds, and cannot accurately reflect the changes in the depth of the hardening layer.
By analyzing the phase composition of the surface of the ductile iron mold, if martensite accounts for more than 95% of the other phases except graphite and less than 5% of the residual austenite, it is determined that the surface hardening effect meets the requirements; the phase composition is analyzed layer by layer along the depth direction, and the end of the martensite + austenite + Fe3C composite sheet layer is used as the mark of the end of the hardening layer, and the depth of the hardening layer is calculated.
The process of determining the surface hardening effect of ductile iron molds is simplified, the accuracy of the judgment results is improved, and the problem of unclearity of hardness and metallographic methods is effectively solved.
Smart Images

Figure CN118241002B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of laser strengthening, and more specifically, to a method for determining the laser surface hardening effect of a ductile iron mold and the depth of a hardened layer. Background Art
[0002] Ductile iron is a high-strength cast iron material with comprehensive properties close to those of steel. It is widely used in the manufacture of parts and large molds in the fields of automobiles, machinery, engineering machinery, and railway transportation. Especially in the field of automobile panels, high-strength ductile iron is often used as raw material because it is low in cost and easy to process. The graphite in the structure has a self-lubricating effect and can effectively reduce friction during production. At the same time, local laser surface strengthening treatment at key mold locations can further increase the mold life.
[0003] The hardness method is usually used to determine the laser surface strengthening process and the depth of the hardened layer. However, this method has great limitations in determining the depth of the laser hardened layer of ductile iron, because ductile iron contains a large amount of spheroidal graphite and there is some ferrite in the hardened layer. When the hardness indentation hits the graphite or ferrite, it cannot correctly reflect the change in the depth of the hardened layer. At the same time, the metallographic method cannot show significant changes in the hardened layer. Therefore, it is not ideal to use the hardness method and metallographic method to determine the laser hardening effect of ductile iron. Summary of the invention
[0004] In view of the defects of the prior art, the present application provides a method for determining the effect of laser surface hardening of ductile iron molds, aiming to solve the problem of complex determination processes of the existing hardness method and metallographic method.
[0005] To achieve the above-mentioned purpose, the present application provides a method for determining the effect of laser surface hardening of a ductile iron mold. The determination method is as follows: a phase composition analysis is performed on the surface of the strengthened ductile iron mold. If, except for graphite, the proportion of martensite in other phases is more than 95% and the proportion of residual austenite is less than 5%, then it is determined that the surface hardening effect of the ductile iron mold meets the requirements.
[0006] Compared with the prior art, the above technical solution conceived by the present application only needs to analyze the surface phase composition of the ductile iron mold to directly determine whether its surface hardening effect meets the requirements, which can achieve the beneficial effects of simple determination process and accurate determination results.
[0007] As a further preference, SEM and / or EBSD are used to perform phase composition analysis on the surface of the strengthened ductile iron mold.
[0008] As a further preferred embodiment, a phase composition analysis is performed on the center position of the laser spot.
[0009] Another object of the present application is to provide a method for determining the depth of the hardened layer of a ductile iron mold, aiming to solve the problem that the hardness method cannot correctly reflect the change in the depth of the hardened layer and the metallographic method cannot show significant changes in the depth of the hardened layer.
[0010] To achieve the above-mentioned purpose, the present application provides a method for determining the depth of the hardened layer of a ductile iron mold laser surface strengthened. The determination method is: performing phase composition analysis on the strengthened ductile iron mold layer by layer along the depth direction, and taking the end of the martensite + austenite + Fe3C composite layer formed on the basis of the original pearlite as the sign of the end of the hardened layer, and then calculating the depth of the hardened layer based on the distance from the surface to the end position of the hardened layer.
[0011] Compared with the prior art, the above technical solution conceived by the present application can effectively improve the accuracy of determining the depth of the hardened layer because the present application adopts the phase composition as a sign of the end of the hardened layer.
[0012] As a further preferred embodiment, the strengthened ductile iron mold is longitudinally sectioned, and then the phase composition analysis is performed layer by layer on the section.
[0013] As a further preferred embodiment, longitudinal sectioning is performed with the center position of the laser spot as the section line.
[0014] As a further preference, SEM and / or EBSD are used to perform phase composition analysis on the strengthened ductile iron mold.
[0015] As a further preferred embodiment, before calculating the hardened layer depth, first observe whether the surface of the ductile iron mold has melted. If there are no protrusions and significant roughness changes on the surface, it is preliminarily determined that the surface has not melted, and the hardened layer depth calculation is continued.
[0016] As a further preferred embodiment, before calculating the hardened layer depth, first determine whether the surface of the ductile iron mold has melted based on the surface phase composition. If there is no ledeburite structure in the surface phase, it is determined that it has not melted, and continue to calculate the hardened layer depth.
[0017] In general, the above technical solutions conceived by this application have the following technical advantages compared with the prior art:
[0018] 1. This application proposes to use the surface phase composition as an evaluation index of the hardening effect, and optimizes the specific evaluation criteria, which can effectively simplify the evaluation process of the surface hardening effect of ductile iron molds, timely feedback and optimize the process design, and has the advantages of simple determination process and accurate determination results, and has strong industrial application value;
[0019] 2. At the same time, the present application also proposes to use phase composition as a sign of the end of the hardened layer, and then calculate the depth of the hardened layer according to the distance from the unmelted surface to the end position of the hardened layer, which effectively solves the problem that the hardness method and metallographic method are unclear in determining the depth of the hardened layer of the ductile iron mold;
[0020] 3. In addition, the present application also optimizes the method for determining the position of the unmelted surface, and proposes using phase composition as the basis for determination, which can further improve the accuracy of the calculation of the hardened layer depth, and the starting position and ending position of the hardened layer depth both use tissue composition as the determination standard, which has the advantages of simple operation and simplified process. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of a method for determining the depth of a hardened layer of a ductile iron mold laser surface strengthening provided in an embodiment of the present application;
[0022] Figure 2 : are the structural characteristic diagrams of the melt layer provided in the embodiments of the present application, wherein (a) is a SEM diagram 50 μm from the surface, (b) is an EBSD phase distribution diagram 50 μm from the surface, (c) is a SEM diagram 300 μm from the surface, and (d) is an EBSD phase distribution diagram 300 μm from the surface;
[0023] Figure 3 It is a structural characteristic diagram of the transition zone between the melting layer and the hardened layer provided in the embodiment of the present application, wherein (a) is a SEM image 500 μm from the surface, and (b) is an EBSD phase distribution image 500 μm from the surface;
[0024] Figure 4 : is a structural characteristic diagram of a hardened layer zone 1 provided in an embodiment of the present application, wherein (a) is a SEM diagram 750 μm from the surface, (b) is an EBSD phase distribution diagram 750 μm from the surface, and (c) is an EBSD bcc phase distribution diagram 750 μm from the surface;
[0025] Figure 5 : are the structural characteristic diagrams of the second zone of the hardened layer provided in the embodiment of the present application, wherein (a) is a SEM diagram 1500 μm from the surface, (b) is an EBSD phase distribution diagram 1500 μm from the surface, and (c) is an EBSD bcc phase distribution diagram 1500 μm from the surface;
[0026] Figure 6 : are the structural characteristic diagrams of the transition zone between the hardened layer and the matrix provided in the embodiments of the present application, wherein (a) is a SEM diagram 1900 μm from the surface, (b) is an EBSD phase distribution diagram 1900 μm from the surface, and (c) is an EBSD bcc phase distribution diagram and a local area phase distribution diagram 1900 μm from the surface;
[0027] Figure 7 This is a diagram of the tissue characteristics of the matrix provided in the embodiments of the present application. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0029] In the description of the present application, it is to be understood that the references in the present specification to "one embodiment"; "one embodiment", "one example" or similar language indicates that a particular feature, structure or characteristic described in conjunction with the embodiment is included in at least one embodiment of the present application. Therefore, the appearance of the phrase "in one embodiment" throughout the present specification of "in one embodiment" and similar language may, but not necessarily, refer to the same embodiment.
[0030] An embodiment of the present application provides a method for determining the effect of laser surface hardening of a ductile iron mold, the determination method being: performing a phase composition analysis on the surface of the strengthened ductile iron mold, if, except for graphite, the proportion of martensite in other phases is more than 95%, and the proportion of residual austenite is less than 5%, then it is determined that the surface hardening effect of the ductile iron mold meets the requirements and is close to the best. Ideally, the phases on the surface of the strengthened ductile iron mold, except for graphite, are all martensitic structures. In actual situations, the proportions of martensite and residual austenite can be further optimized according to demand.
[0031] Compared with the prior art, the above technical solution conceived by the present application only needs to analyze the surface structure of the ductile iron mold to directly determine whether its surface hardening effect meets the requirements, which can achieve the beneficial effects of simple determination process and accurate determination results.
[0032] Furthermore, SEM and / or EBSD are used to analyze the phase composition of the surface of the strengthened ductile iron mold. Preferably, EBSD is used to analyze the phase composition of the surface of the strengthened ductile iron mold, which can more clearly determine the type and content of each organization compared with SEM.
[0033] Furthermore, the phase composition analysis can be performed on the center position of the laser spot, and the phase composition analysis can be performed directly on the surface of the ductile iron mold, or a longitudinal section can be performed along the center position of the laser spot, and then the phase composition analysis can be performed on the top layer, which is convenient for the subsequent measurement of the hardened layer depth.
[0034] like Figure 1As shown, another embodiment of the present application provides a method for determining the depth of the hardened layer of a ductile iron mold laser surface strengthened, and the determination method is: performing phase composition analysis on the strengthened ductile iron mold along the depth direction, taking the end of the martensite + austenite + Fe3C composite layer formed on the basis of the original pearlite as a sign of the end of the hardened layer, and then calculating the depth of the hardened layer based on the distance from the surface to the end position of the hardened layer.
[0035] Through the above technical scheme conceived by the present application, compared with the prior art, since the present application adopts phase composition as the sign of the end of the hardened layer, it can effectively improve the accuracy of determining the depth of the hardened layer and solve the problem of inaccuracy of the hardness method and metallographic method in determining the depth of the hardened layer of ductile iron materials.
[0036] Furthermore, the strengthened ductile iron mold was longitudinally sectioned using the center of the laser spot as the section line, and then the section was subjected to a microstructure analysis. Since the energy at the center of the laser spot was the highest, the maximum depth of the hardened layer could be obtained by using the center of the laser spot as the section line.
[0037] Furthermore, the structural composition of the strengthened ductile iron mold is analyzed by SEM and / or EBSD. Since both SEM and EBSD can achieve fast and continuous scanning, they are not only more efficient than the dot analysis method, but also have more accurate test results.
[0038] Further, considering that the surface melting of the ductile iron mold has a great influence on its surface roughness, and because of its poor surface quality, it is not suitable for use as a workpiece for final heat treatment, it is necessary to determine whether its surface has melted before calculating the depth of the hardened layer. Whether the surface of the ductile iron mold has melted can be determined by visual observation. If there is no protrusion on the surface and a significant change in roughness, it is preliminarily determined that the surface has not melted, and the calculation of the depth of the hardened layer is continued. More preferably, whether the surface of the ductile iron mold has melted can be determined by the phase composition of the surface. If there is no ledeburite structure in the phase on the surface, it is determined that it has not melted, and the calculation of the depth of the hardened layer is continued. Using phase composition as a basis for judgment can not only effectively solve the problem of inaccurate visual observation, but also does not require any additional detection, which can effectively improve the detection efficiency of the depth of the hardened layer and reduce the detection cost.
[0039] The method for determining the laser surface hardening effect and hardened layer depth of ductile iron molds provided in this application is mainly based on the following principles. After the ductile iron is melted by laser surface quenching, the changes from the surface to the matrix are divided into five stages, as follows:
[0040] Stage 1: Melting Layer
[0041] After the melting zone is self-quenched, the graphite is completely dissolved due to the high surface temperature. Figure 2 As shown, the main structural feature of the molten layer is the structure of a part of needle-shaped martensite distributed in the austenite in the ledeburite.
[0042] Stage 2: Transition zone between molten layer and hardened layer
[0043] like Figure 3 As shown in the figure, the amount of ledeburite gradually decreases in the transition area between the melting layer and the hardened layer. Due to the action of the laser, the graphite in this area is partially dissolved, and the original ferrite and pearlite are completely transformed into austenite. The carbon content in austenite is relatively high, which reduces the starting and ending temperatures of the martensite transformation, retains a large amount of residual austenite, and thus generates a transition layer dominated by residual austenite and martensite during the self-quenching process. On the side close to the hardened layer, as the quenching temperature gradually decreases, the graphite dissolves less and less, and the starting and ending temperatures of the martensite transformation increase, causing the amount of martensite to gradually increase.
[0044] Stage 3: Hardened layer
[0045] The hardened layer can be divided into two regions, such as Figure 4 As shown in the figure, the first area of the hardened layer is mainly composed of graphite, a large amount of martensite and a small amount of retained austenite (except for graphite, martensite accounts for more than 95% and retained austenite accounts for less than 5%). This layer has excellent hardness. Therefore, the organizational characteristics of graphite, a large amount of martensite and a small amount of retained austenite represent the sign that the surface layer can obtain close to the highest hardness. Gradually transition to the interior of the material, such as Figure 5 As shown, the second zone of the hardened layer retains a large amount of ferrite, and the hardness gradually decreases. At this time, the martensite is mainly formed by the transformation of the original pearlite structure into austenite after quenching.
[0046] Stage 4: Transition zone between hardened layer and matrix
[0047] like Figure 6 As shown in the figure, the transition zone near the hardened layer is a composite structure of graphite, ferrite, martensite + austenite + Fe3C. Considering that the ledeburite after quenching is also a composite structure of martensite + austenite + Fe3C, but its microstructure is fishbone-shaped, and the martensite + austenite + Fe3C in the hardened layer near the matrix transition zone is a composite lamellar structure formed on the basis of original pearlite. Therefore, the end of the martensite + austenite + Fe3C composite lamellar structure formed on the basis of original pearlite is used as a sign of the end of the hardened layer.
[0048] Stage 5: Matrix
[0049] like Figure 7 As shown, the matrix is graphite, ferrite and pearlite.
[0050] Based on the above principles, this application uses the surface organization of graphite, martensite and a small amount of residual austenite, in which, except for graphite, martensite accounts for more than 95% and residual austenite accounts for less than 5%, as the evaluation standard for determining whether the laser quenching process used has achieved a good surface hardening effect. This method can directly judge the process effect from the surface organization, thereby providing a key reference basis for process optimization. At the same time, this application also uses the end of the martensite + austenite + Fe3C composite layer formed on the basis of the original pearlite as a sign to determine the end of the hardened layer, and the total hardened layer depth is the distance from the surface to the end position of the hardened layer. This method can solve the problem that the hardness method and metallographic method are unclear in determining the hardened layer depth of ductile iron materials.
[0051] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A method for determining the depth of the laser surface hardening layer of a ductile iron mold, characterized in that: The determination method is as follows: laser surface strengthening is performed on a ductile iron mold containing ferrite, and phase composition analysis is performed layer by layer on the strengthened ductile iron mold along the depth direction, and the end of the martensite + austenite + Fe3C composite layer formed on the basis of the original pearlite is used as a sign of the end of the hardened layer, and whether the surface of the ductile iron mold melts is determined, and then the depth of the hardened layer is calculated according to the distance from the unmelted surface to the end position of the hardened layer.
2. The method for determining the depth of the laser surface hardening layer of a ductile iron mold according to claim 1, characterized in that: The strengthened ductile iron mold was longitudinally sectioned, and then the phase composition analysis was performed layer by layer.
3. The method for determining the depth of the laser surface hardening layer of a ductile iron mold according to claim 2, characterized in that: The center position of the laser spot is used as the section line for longitudinal sectioning.
4. The method for determining the depth of the laser surface hardening layer of a ductile iron mold according to claim 1, characterized in that: The phase composition of the strengthened ductile iron mold was analyzed by SEM and / or EBSD.
5. The method for determining the depth of the laser surface hardening layer of a ductile iron mold according to any one of claims 1 to 4, characterized in that: Before calculating the depth of the hardened layer, first observe whether the surface of the ductile iron mold has melted. If there are no protrusions or significant changes in roughness on the surface, it is preliminarily determined that the surface has not melted, and the calculation of the hardened layer depth can be continued.
6. The method for determining the depth of the laser surface hardening layer of a ductile iron mold according to any one of claims 1 to 4, characterized in that: Before calculating the hardened layer depth, first determine whether the surface of the ductile iron mold has melted based on the surface phase composition. If there is no ledeburite structure in the surface phase, it is determined that it has not melted, and continue to calculate the hardened layer depth.